1994
DOI: 10.1093/jnci/86.6.431
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Mammographic Densities Induced by a Hormonal Contraceptive Designed to Reduce Breast Cancer Risk

Abstract: The reduced estrogen and progestogen exposures to the breast that were achieved by the hormonal contraceptive regimen resulted in substantial reductions in follow-up mammographic densities at 1 year compared with baseline. Although there is no direct evidence that such a reduction in densities will lead to a reduced risk of breast cancer, indirect evidence for a protective effect of this regimen is that early menopause reduces breast cancer risk, and that menopause is associated with a reduction in mammographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(69 citation statements)
references
References 0 publications
1
67
0
1
Order By: Relevance
“…Other exposures of potential interest in this context include tamoxifen (27), a gonadotrophin-releasing hormone agonist (28), and a low-fat highcarbohydrate diet (29). Although all of these factors are known to influence mammographic density, for none of them is it yet known whether the effects of these variables on density mediate their effects on risk.…”
Section: Discussionmentioning
confidence: 99%
“…Other exposures of potential interest in this context include tamoxifen (27), a gonadotrophin-releasing hormone agonist (28), and a low-fat highcarbohydrate diet (29). Although all of these factors are known to influence mammographic density, for none of them is it yet known whether the effects of these variables on density mediate their effects on risk.…”
Section: Discussionmentioning
confidence: 99%
“…For example, MR measurements could be used to investigate the development of the breast parenchymal patterns with age in high risk subjects, or to assess potential preventative intervention strategies, such as the use of hormone supplements for reducing risk of breast cancer (Spicer et al, 1994), use of tamoxifen (Nayfield et al, 1991) or dietary modification (Boyd et al, 1990). The role of MR parameters in determining strategies for breast cancer screening remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that women on the contraceptive regimen showed significant (P = 0.039) reduction in mammographic densities between the baseline and 1-year mammograms, compared with control group. In a follow-up of this study (Spicer et al, 1994), 12 months after completion of treatment, the mean percentage of mammographic density in the treated group was no different from that at baseline (P = 0.73). Reductions in mammographic density for this special contraceptive regimen (GnRHA plus low-dose add-back estrogen-progestin) persist only during treatment period.…”
Section: Gonadotropin-releasing Hormone Agonistsmentioning
confidence: 61%
“…A special designed contraceptive study (Spicer et al, 1994) randomly assigned 21 patients, 27-40 years of age, with a 5-fold greater than normal risk of breast cancer, in a 2:1 ratio to special contraceptive group (14 women who received GnRHA (leucoprolide acetate) plus very low doses add-back conjugated estrogen and medroxyprogesterone acetate) or to a control group (7 women). The authors found that women on the contraceptive regimen showed significant (P = 0.039) reduction in mammographic densities between the baseline and 1-year mammograms, compared with control group.…”
Section: Gonadotropin-releasing Hormone Agonistsmentioning
confidence: 99%